The Impact of Social Media on The Interaction Patterns of The Community in Rujak Ngalun, Mekar Sari Village, Praya Barat District, Central Lombok - Hajar, Siti; Ningsih, Dewi Puspita; Fauzan, Ahmad; Apriawan, Andika; Haryono, Haryono (Global Journal of Social Learning, 2024)
The rapid advancement of technology has led to a decline in verbal communication activities, impacting many aspects of daily life, particularly social interaction. The researcher assumes that social media serves as a platform for interactive engagement, both personally and in groups. Consequently, this study aims to examine the impact of social media on the interaction patterns of the community in Rujak Ngalun, Mekar Sari Village, Praya Barat District, Central Lombok. This research employs a qualitative method grounded in positivist philosophy. The data analysis is qualitative in nature, emphasising meaning over generalisation. Social media is a platform that provides various features enabling users to engage in digital activities in their daily lives. In the Rujak Ngalun community, social media serves as a comprehensive and user-friendly medium for social interaction, facilitating long-distance communication.